Changes in organic carbon and nitrogen in soil with metal pollution by Cd, Cu, Pb and Zn: a meta‐analysis. (March 2016) - Zhou, T.; Li, L.; Zhang, X.; Zheng, J.; Zheng, J.; Joseph, S.; Pan, G.
Summary: Organic carbon (OC) and nitrogen (N) storage in soil plays an important role in global climate change and in maintaining food security. Pollution of soil with heavy metals has occurred in many parts of the world, but their effects on soil OC and N have not been well addressed. Relevant data were extracted from peer‐reviewed journal papers and analysed by a meta‐analysis to determine how long‐term heavy metal pollution affected soil OC and N status. Plant biomass decreased significantly because heavy metals in soil decreased soil OC and N concentrations by 5.0 and 17.9%, respectively, but increased the C/N ratio by 5.1%. The largest reductions in soil OC and N concentrations were in soil more strongly polluted by metals. The changes in soil OC and N with metal pollution varied with climatic conditions. More substantial decreases in OC and N concentrations were likely to occur in polluted soil with large background contents of OC and low pH. Overall, heavy metals were linked to greater reductions in soil OC and N concentrations in natural ecosystems than in agro‐ecosystems. These results provided a quantitative evaluation of the effects of heavy metal pollution on the decrease in soil C and N concentrations and, therefore, on global climate change. Further consideration should be given to changes in the cycling of C and N in soil polluted with metals in natural and agro‐ecosystems. Highlights: Organic carbon (OC) and total nitrogen (TN) of metal polluted soil were evaluated. The results of meta-analysis showed that pollution decreased soil OC and TN, but increased C/N ratio. The responses to heavy metals were concentration dependent. Responses varied with soil properties, ecosystems and climatic differences.